Procreation tax incentives : a quantification of the tax savings and an analysis of its fluctuations over time. - Ho, Hwee Woon. (2008)
This paper seeks to estimate the value of the procreation benefits that accrue to married couples across the income strata. Simultaneously, it investigates how the value of these tax savings change over time. The procreation incentive changes introduced via population policies are incorporated into a trend analysis.